Organ Culture of Newborn Piglets’ Thyroid Gland as an Object for Cryopreservation - Lugovoj, S. V.; Bondarenko, T. P.; Gubina, N. F.; Olefirenko, A. I.; Olefirenko, A. A. (Problems of Cryobiology and Cryomedicine, 2006)
The investigation of functional characteristics for organ culture of thyroid gland of new born piglets (OCThGNP) was carried-out during its culturing for 10 days in nutrient media of different composition.